Toward Digital Transformation: Insights into Chinese Cross-Border E-Commerce SMEs During the COVID-19 Pandemic and the Post-Pandemic Era - Arthur William Fodouop Kouam (SAGE Open)
The pandemic and its restrictions have forced businesses to rethink their strategies and daily operations. The originality of this research lies in assessing the unique challenges cross-border e-commerce Small and Medium Enterprises (SMEs) faced during the pandemic and the strategies they developed to survive. This study also explores the novel practices that emerged during the same period and the digital transformation of these SMEs. Data were gathered through interviews, observation, and questionnaires from 104 cross-border e-commerce SMEs based in China. The study used thematic analysis and descriptive statistics to interpret data. Qualitative Comparative Analysis (QCA) was also used to obtain insights into the configurations of resilience strategies leading to SMEs’ digital transformation. Findings show that cross-border e-commerce SMEs suffered financially during the pandemic. In addition, they faced marketing, logistics, and supply chain challenges. However, they developed various strategies to cope with those challenges and survive in a period of uncertainty. This research suggests a new business model of cross-border e-commerce based on SMEs’ novel practices and configuration strategies to obtain digital transformation. Cross-border e-commerce SMEs should upgrade their marketing, financial, supply chain, and logistics strategies based on the findings of this study. They should leverage technology, diversify their supply chain, adopt online marketing strategies, focus on customer service, optimize their cash flow, and explore new markets.